Hybrid scanning electrochemical cell microscopy-interference reflection microscopy (SECCM-IRM): tracking phase formation on surfaces in small volumes. (15th December 2021) - Valavanis, Dimitrios; Ciocci, Paolo; Meloni, Gabriel N.; Morris, Peter; Lemineur, Jean-François; McPherson, Ian J.; Kanoufi, Frédéric; Unwin, Patrick R.
Abstract : Interference reflection microscopy allows real-time visualisation of the scanning electrochemical cell microscopy meniscus and nanoscale features within it. Abstract : We describe the combination of scanning electrochemical cell microscopy (SECCM) and interference reflection microscopy (IRM) to produce a compelling technique for the study of interfacial processes and to track the SECCM meniscus status in real-time. SECCM allows reactions to be confined to well defined nm-to-μm-sized regions of a surface, and for experiments to be repeated quickly and easily at multiple locations. IRM is a highly surface-sensitive technique which reveals processes happening (very) close to a substrate with temporal and spatial resolution commensurate with typical electrochemical techniques. By using thin transparent conductive layers on glass as substrates, IRM can be coupled to SECCM, to allow real-time in situ optical monitoring of the SECCM meniscus and of processes that occur within it at the electrode/electrolyte interface. We first use the technique to assess the stability of the SECCM meniscus during voltammetry at an indium tin oxide (ITO) electrode at close to neutral pH, demonstrating that the meniscus contact area is rather stable over a large potential window and reproducible, varying by only ca. 5% over different SECCM approaches. At high cathodic potentials, subtle electrowetting is easily detected and quantified. We also look inside the meniscus to reveal surface changes at extreme cathodic potentials, assigned to the possible formation of indium nanoparticles. Finally, we examine the effect of meniscus size and driving potential on CaCO3 precipitation at the ITO electrode as a result of electrochemically-generated pH swings. We are able to track the number, spatial distribution and morphology of material with high spatiotemporal resolution and rationalise some of the observed deposition patterns with finite element method modelling of reactive-transport. Growth of solid phases on surfaces from solution is an important pathway to functional materials and SECCM-IRM provides a means for in situ or in operando visualisation and tracking of these processes with improved fidelity. We anticipate that this technique will be particularly powerful for the study of phase formation processes, especially as the high throughput nature of SECCM-IRM (where each spot is a separate experiment) will allow for the creation of large datasets, exploring a wide experimental parameter landscape.